The Chinese University Students' English Reading Strategies: An Analysis of the Current Situation and A Proposal for Enhancement - ZHENG, Rui (Pacific International Journal, 2023)
English reading strategies and awareness of reading strategies are of great significance for English learners to master and possess high English reading abilities, but in reality, learners' ability to apply English reading strategies is still unsatisfactory. Moreover, this issue seems to be a common and urgent issue for all learners of English as a second language. This study taking a Chinese university (Hunan University of Science and Engineering, HUSE) as an example, using the Survey of Reading Strategies (SORS) to measure three broad categories of reading strategies, 527 respondents involved, through comparing data mean values of English majors with non-English majors and the composite mean value of these respondents, found that: (a) English major students have higher reading strategy awareness than non-English major students; (b) English major and non-English major students are at different levels in terms of reading strategy awareness and generally have a moderate level of reading strategies; (c) There is great room for improvement in university students’ reading strategy. Centering on how to make good use of the teaching resources of reading courses and how to use innovative ways and methods to enhance the awareness and ability of college students' reading strategies, this study puts forward four measures, namely, attaching importance to reading strategy education in reading course teaching, attaching importance to the leading role of reading course teachers in improving students' reading strategy level in curriculum teaching, attaching importance to students' main role, and strengthening students' reading strategy training.